Improving Imaging Modalities in Early Psoriatic Arthritis: The Role of Ultrasound in Early Diagnosis of Psoriatic Arthritis - Gudu, Tania; Ng, Beverly; Jethwa, Hannah; Graham, Catherine; Kudva, Veda; Rammanohar, Jashmitha; Zhang, Chen; Sapsford, Mark; Jadon, Deepak R. (Frontiers in Medicine, 2022)
Objective: Despite recent advances, early diagnosis of psoriatic arthritis(PsA) remains a challenge. Ultrasound (US) could be a useful tool for the diagnosis and management of PsA. The objective of this review was to determine the role of US in early diagnosis of PsA. Methods: We performed a literature review aiming to evaluate studies on US findings in psoriasis and their predictive value of progression to PsA, as well as studies on US features specific for PsA compared to other conditions. Results: A total of 40 studies were included. Sixteen studies assessed US findings in psoriasis; only 3 prospectively evaluated the role of US in predicting progression to PsA. PsA patients had a greater frequency of US abnormalities, in particular enthesitis and Power Doppler(PD) signal compared to patients with psoriasis only. In the longitudinal studies, psoriatic patients with higher enthesopathy scores at baseline were more likely to progress to PsA. Twenty-four studies evaluated US abnormalities in PsA in comparison with other conditions. Most specific US features that distinguish PsA from psoriasis were PD signal and erosions in joints and entheses. Extra-synovial changes (PD peritendinous soft tissue oedema, flexor tendon enthesopathy and thickening of the pulleys) were highly characteristic for PsA compared to rheumatoid arthritis. Entheseal erosions and PD signal were more frequent in PsA than in fibromyalgia patients. Conclusion: More research is needed to identify predictive factors of progression to PsA in patients with psoriasis, as well as to determine the most specific US features that differentiate PsA from other conditions.